Psychological characteristics of the relationship between mental health and hardiness of Ukrainians during the war - Predko, Viktoriia; Schabus, Manuel; Danyliuk, Ivan (Frontiers in Psychology, 2023)
The aim of our survey is to identify psychological features for the relationship between mental health and hardiness of Ukrainians during the war.Methods: The study involved 608 Ukrainians. We aimed to identify the relationship between mental health and hardiness and determine the differences in the peculiarities of mental health of people with different levels of hardiness. Also we looked for predictors for hardiness.Results: Subjective hardiness was found to be related to specific manifestation of mental health in the Ukrainian population. Strong correlations were revealed for hardiness with adaptation (ρ=0.818), emotional comfort (ρ=0.786), internality (ρ=0.672), self-perception (ρ=0.656,), escapism (ρ= -0.632) and mental health (ρ=0.629). A prognostic model based on linear regression analysis identified the main predictors of personal hardiness and confirmed correlational analysis. Mental health (0.341), emotional comfort (ρ=0.786), and escapism (-0.576) were found to be good predictors. Altogether 40.1% of Ukrainians scored low, 54.6% medium, and 5.3% high on individual hardiness.The study found that about every 4th Ukrainian demonstrates a low level of personal hardiness, which is accompanied by emotional discomfort and lack of internal locus of control, making them more susceptible to stress and illness. Additionally, they tend to distance themselves which significantly exacerbates the situation. It has been found that Ukrainians with low levels of personal hardiness exhibit escapism (with diversion of the mind to imaginative activity), a destructive defense mechanism that not only prevents effective problem solving but also has long-term negative consequences for their overall health. Consequently, especially people with low hardiness should receive specific support to stabilize their mental wellbeing and health overall.